PENGARUH KUALITAS PRODUK, CITRA MEREK DAN PERSEPSI HARGA TERHADAP KEPUTUSAN PEMBELIAN (Studi pada Konsumen Sepeda Motor Honda Beat di Kota Semarang) - Miftah Wahyu Ariani, 12.05.51.0106 (Students' Journal of Economic and Management, 2017)
The purpose of this study was to determine the effect of the product quality, brand image and perception of price on purchase decisions (studies on consumer Honda Beat motorcycle in Semarang). The sampling method inthis study using purposive sampling research using surveys and questionnaires to 100 respondents in Semarang City. The analytical method used in this study is multiple regresion analysis. It was found that the product quality and significant positive effect on purchasing decisions Honda Beat motorcycle in the city of Semarang. However, it was found that the brand image is not positive and significant effect on purchasing decisions Honda Beat in Semarang. While the price perception of positive and significant effect on purchasing decisions Honda Beat in Semarang. Adjusted R Square value of 0,585 can illustrate that the dependent variable is explained by the independent variable variabelitas for 58,5%, while 41,5% are influenced by the other variables. Keywords: Quality Product, Brand Image, Price Perception, and Purchase Decision